A PROSPECTIVE STUDY ON PROCALCITONIN AS AN USEFUL BIOMARKER FOR PROGNOSIS OF SEPSIS AND GUIDE FOR ANTIBIOTIC THERAPY IN SICU PATIENTS (Asian Journal of Medical Research and Health Sciences, 2026)
Background of the study: Sepsis is most common cause of death in surgical ICU patients. Early diagnosis and appropriate antibiotics play the major role in saving the patients.  Procalcitonin helpful in early detection as well as to monitor the anti-microbial therapy. Aims and Objectives: To study on effectiveness of procalcitonin as a useful biomarker for prognosis of sepsis and guide for antibiotic therapy in SICU patients. Material and Methods: Cases admitted to GMKMC hospital Salem with signs of sepsis in SICU patients will be closely monitored from the day of admission to the day of discharge. On an average of 100 cases with signs of sepsis in ICU patients admitted between 2017 to 2019. Results: A Prospective study on Procalcitonin as a useful biomarker for prognosis of sepsis and guide for antibiotic therapy in SICU patients revealed the following findings. The mean age is 57.06 years with a standard deviation of 9.39 years. Majority of the participants were males (n=56, 56%) while the rest were females. Out of the 100 patients, 76 of them (76%) were blood culture positive while the remaining 24% were blood culture negative. 68 of them (68%) were pus culture positive while the remaining 32% were pus culture negative. Among the 100 patients, 66 of them (66%) were wound swab positive while the remaining 34% were wound swab negative. 42% were Klebsiella positive and remaining were various other organisms. The organisms were sensitive to Piptaz (50%) and Cefoperazone (48%). Procalcitonin is 100% sensitive and specific in predicting the prognosis in patients of surgical ICU.  Conclusion: Procalcitonin levels rise rapidly in sepsis and typically peak earlier than C-reactive protein (CRP). They also decline more quickly in response to effective treatment. Consequently, procalcitonin is useful both for the early detection of sepsis and for monitoring the response to therapy, making it an ideal biomarker in the management of sepsis.